Behind the scenes – Rigour of a Master’s clinical and counselling psychology degree selection process - Derwin, R.; Spies, R.; Coetzee, H. (South African Journal of Higher Education, 2023)
This article reports on the rigour of a selection process for master’s degree programmes in clinical and counselling psychology at an undisclosed university in South Africa over a six-year period (n=81). This was achieved by completing correlation and regression analyses between the six selection activities, the six course modules, and the course average in the student’s M1 year. Results showed significant positive regressions between the metaphors activity, child psychopathology, and theory of psychological interventions modules, between the research task and neuropsychology, between the psychopharmacology and psychopathology modules, and between the problem-solving activity and the course average. The case study activity negatively predicted the ethics and practical work and applied and community psychology modules. The conclusion was that the selection process can be considered valid, as the skills assessed for most of the selection activities positively correlated and predicted the skills required to succeed both academically in the M1 year and as a practising psychologist. However, the case study activity required further investigation, as the skills that are purportedly assessed should correlate and positively predict the ethics and practical work module, which was not the case. Future studies should also investigate the usefulness of interviews during this process.